Expectations versus reality: motivational outcomes of unmet course-specific expectations in higher education - Sander, Zoe; Rieder, Vivien; Spinath, Birgit (International journal of educational research, 2025)
At the beginning of a new academic term, higher education students hold a variety of course-specific expectations (e.g., related to the course content). A mismatch between students’ expectations and the course reality may contribute to the often-found motivational decline over the academic term and unfavorable academic outcomes. The current study examines the relationship between unmet course-specific expectations in an educational psychology lecture course and the early motivational drop as well as learning-related outcomes. N = 898 teacher and psychology students participated at five measurement points across an academic term. Students rated the extent to which they anticipated gaining a general overview of the content, learning scientific methods of educational psychology, and receiving practical tips as well as the degree to which they had learned these contents in the course. Using the theoretical framework of Situated Expectancy-Value Theory, we assessed students' ability self-concept and task values at each measurement point. Additionally, several learning outcomes were evaluated at the end of term. Students noted discrepancies in expected versus actual content, which were more evident among teacher students. Higher levels of unmet expectations were linked to steeper motivational declines and poorer learning outcomes at the end of the term. Results suggest that the mismatch between students’ expectations and actual course content is crucial in influencing motivational development and learning success. Theoretical and practical implications are discussed.
Gesehen am 26.01.2026